BRAF V600E status may facilitate decision-making on active surveillance of low-risk papillary thyroid microcarcinoma. (January 2020) - Kim, Kyeong J.; Kim, Sin G.; Tan, Jie; Shen, Xiaopei; Viola, David; Elisei, Rossella; Puxeddu, Efisio; Fugazzola, Laura; Colombo, Carla; Jarzab, Barbara; Czarniecka, Agnieszka; Lam, Alfred K.; et al.
Abstract: Introduction: Conservative active surveillance has been proposed for low-risk papillary thyroid microcarcinoma (PTMC), defined as ≤1.0 cm and lacking clinical aggressive features, but controversy exists with accepting it as not all such PTMCs are uniformly destined for benign prognosis. This study investigated whether BRAF V600E status could further risk stratify PTMC, particularly low-risk PTMC, and can thus help with more accurate case selection for conservative management. Methods: This international multicenter study included 743 patients treated with total thyroidectomy for PTMC (584 women and 159 men), with a median age of 49 years (interquartile range [IQR], 39–59 years) and a median follow-up time of 53 months (IQR, 25–93 months). Results: On overall analyses of all PTMCs, tumour recurrences were 6.4% (32/502) versus 10.8% (26/241) in BRAF mutation-negative versus  BRAF mutation-positive patients ( P = 0.041), with a hazard ratio (HR) of 2.44 (95% CI (confidence interval), 1.15–5.20) after multivariate adjustment for confounding clinical factors. On the analyses of low-risk PTMC, recurrences were 1.3% (5/383) versus 4.3% (6/139) in BRAF mutation-negative versus  BRAF mutation-positive patients, with an HR of 6.65 (95% CI, 1.80–24.65) after adjustment for confounding clinical factors. BRAF mutation was associated with a significant decline in the Kaplan–Meier recurrence-free survival curve in low-risk PTMC. Conclusions: BRAF V600E differentiates the recurrence risk of PTMC, particularly low-risk PTMC. Given the robust negative predictive value, conservative active surveillance of BRAF mutation-negative low-risk PTMC is reasonable whereas the increased recurrence risk and other well-known adverse effects of BRAF V600E make the feasibility of long-term conservative surveillance uncertain for BRAF mutation-positive PTMC. Highlights: BRAF V600E status further differentiates the recurrence risk of low-risk papillary thyroid microcarcinoma (PTMC). BRAF mutation has a robust negative predictive value for recurrence of low-risk PTMC. Conservative management of low-risk PTMC with wild-type BRAF is reasonable.